Clinicо-anamnestic characteristics of children with atopic dermatitis - R. M. Fayzullina; Z. A. Shangareeva; A. V. Sannikova; A. F. Mananova; L. M. Kabirova; A. R. Idrisova (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
.